Editorial Perspective: Prato Research Collaborative for change in parent and child mental health – principles and recommendations for working with children and parents living with parental mental illness. (28th September 2021) - Reupert, Andrea; Bee, Penny; Hosman, Clemens; van Doesum, Karin; Drost, Louisa M.; Falkov, Adrian; Foster, Kim; Gatsou, Lina; Gladstone, Brenda; Goodyear, Melinda; Grant, Anne; Grove, Christine; et al.
Abstract : Children whose parents have mental illnesses are among the most vulnerable in our communities. There is however, much that can be done to prevent or mitigate the impact of a parent's illness on children. Notwithstanding the availability of several evidence‐based interventions, efforts to support these children have been limited by a lack of adequate support structures. Major service reorientation is required to better meet the needs of these children and their families. This editorial provides recommendations for practice, organisational, and systems change.